Metodyczne aspekty modelowania struktury majątku obrotowego w koncepcji synchronizacji zarządzania płynnością finansową - Zabolotnyy, Serhiy (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
In the article the metod of identification and evaluation of the relations between the seasonality of sales and structure of current assets are viewed on the expample of a manufacturing joint-stock company Wilbo S.A. An approach to the optimalization of the actual strategy of liquidity according to the matching principle is presented. The research indicated the relations between the level of current assets and sales seasonality: sales growth determined the increase of current assets and sales reduction led to decrease of current assets. According to matching principle no relations were determined between the structure and level of the components of current assets and seasonality. An optimalization of current assets’ structure enabled reduction of inventory level and increase of accounts receivable in the periods of sales’ maximization along with the maximization of cash in periods of sales’ decrease.